Material properties of the seal gasket for shield tunnels: A review. (10th December 2018) - Yang, Chen; Shen, Shui-Long; Hou, Dong-Wei; Liao, Shao-Ming; Yuan, Da-Jun
Highlights: Gasket materials include two categories: (i) elastic gasket and (ii) hydrophilic composite. Sealing principles between elastic gasket and hydrophilic composite gasket are compared. Methods to predict the service life of rubber materials are introduced. Self-healing technique for polymeric materials for gasket is discussed. Perspectives for future developments of new materials of seal gaskets are proposed. Abstract: This paper reviews the material properties of the seal gaskets of shield tunnels. In order to understand the function of sealing gaskets, the significance and structure of gaskets in tunnel segments are briefly introduced. Then, the material types of gasket are presented. Gasket materials include two categories: (i) the traditional elastic gasket and (ii) the hydrophilic composite elastic gasket. The traditional elastic gasket is composed of chloroprene rubber (CR) and ethylene propylene diene rubber (EPDM), in which the sealing function is implemented as a result of the elastic properties of the materials. The hydrophilic composite elastic gasket includes vulcanized water swelling rubber (WSR) and water swelling polyurethane (WSP), in which the sealing function is obtained from both the elastic properties and the water absorption ability of the gasket material. CR and EPDM were the earliest materials used in engineering practice; however, EPDM is the main material of the gasket today. The sealing mechanism of both CR and EPDM is presented at the molecule level. After that, the water absorption process for both WSR and WSP in hydrophilic composite is reviewed. Methods to improve the sealing behavior of WSR are also summarized. Furthermore, the aging of the gasket material is discussed. Finally, perspectives for future developments of new materials or ways to improve the performance of seal gaskets are proposed.